PERLINDUNGAN HUKUM TERHADAP KOPERASI SERBA USAHA PEREMPUAN BERKAT ATAS KERUGIAN AKIBAT KREDIT MACET: TINJAUAN DARI PERSPEKTIF HUKUM PERDATA - Jaden Alexandro Lango; Darius Mauritsius; Rini Marselin Kaesmetan (STKIP Subang, 2026)
This study examines the legal protection afforded to Koperasi Serba Usaha (KSU) Perempuan Berkat against losses resulting from non-performing loans from a civil law perspective. The research employs an empirical legal method with a qualitative approach conducted at KSU Perempuan Berkat in Fatufeto Village, Alak District, Kupang City. Data were collected through interviews, documentation, and literature review involving cooperative administrators, members with non-performing loans, and representatives from the Cooperative Office. The findings indicate that non-performing loans are primarily caused by factors related to character, capacity, capital, and economic conditions of members, while collateral has generally been fulfilled as a loan security requirement. Legal protection for the cooperative is implemented through preventive measures, including the application of the 5C principle, supervision, member education, and collateral requirements, as well as repressive measures such as warning letters, loan renegotiation, and loan restructuring. However, the implementation of legal protection has not been optimal because the cooperative prioritizes a familial approach over formal legal actions. Therefore, strengthening prudential principles and consistent law enforcement is necessary to minimize losses arising from non-performing loans and ensure the sustainability of cooperative operations.